PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL EFFICACY OF ALLIUM PORRUM EXTRACTS - T. USHADEVI; R. SATHYA; R. SHANMUGAPRIYA; K.ANANDHI (International Journal of Pharma and Bio Sciences, 2013)
Phytochemical constituents of Allium porrum leaf extracts and its antibacterial potentialities were evaluated using different solvents. Phytochemical screening of the different extracts showed that leaves contains important compounds such as amino acid with sulphate, carbohydrates, Phenols, Proteins, flavonoids, alkaloids, steroids, Tannins and saponin. Aqueous, methanol and acetone extracts of plant leaves were used for assessing antibacterial activity against Salmonella typhi, Klebsiella pneumonia, Staphylococcus aureus, Pseudomonas aeruginosa and Proteus vulgaris by agar well diffusion method. The present study demonstrated that the aqueous, methanolic, acetone extracts of A. porrum consists different phytochemical components thus exhibit variations in the antibacterial activity. These promissory extracts open the prospect of finding new clinically effective antibacterial compounds.